The Influence of ZIS, Poverty, Education, and Unemployment on the Indonesian Human Development Index (2019-2021) - Habibi, Faisol; Febrianti, Lutfia Adha (Universitas Siliwangi, 2024)
AbstractIntroduction to The Problem: The Human Development Index is an important indicator that can measure and describe the quality of life of Indonesian people. In improving the quality of life, Islam has a philanthropic instrument, namely ZIS, to help improve people's lives.Purpose/Objective Study: The aim of this research is to analyze four factors that can influence the human development index (HDI) in Indonesia, namely ZIS (zakat, Infaq, Sadaqoh), Poverty, Education, and Unemployment.Design/Methodology/Approach: The approach used in this research is a quantitative approach. Statistical data analysis using Stata with panel data regression analysis methodFindings: The research results found that partially the ZIS variable, poverty and education variables had a significant effect on the human development index in Indonesia in 2019-2021, while the unemployment variable had an insignificant effect on the human development index in Indonesia in 2019-2021. influence on the human development index in Indonesia in 2019-2021. Meanwhile, the results simultaneously show that the variables ZIS, poverty, education and unemployment have a significant effect on the human development index in Indonesia in 2019-2021.Paper Type: Research Article